A self-learning framework for services selection. (2nd December 2009) - Wang, H.; Wang, Y.; Huang, J.Z.; Xu, X.
Service-Oriented Architecture (SOA) is emerging as a new paradigm for integration of heterogeneous application systems within an enterprise and between enterprises. Web services are widely considered as enabling technologies for implementing application services under SOA. Web services composition is a flexible means to build various application services. In web services composition, one primary task is to discover and select proper services according to user requests and preferences. In this paper, we present SLF4SS, a self-learning framework for services selection.